Contesting Illness : Process and Practices - Teghtsoonian, Katherine; Moss, Pamela, 1960- (Book collections on Project MUSE., 2008)
The relationship between power and illness is the subject of limited discussion despite it being one of the most important issues in health-related policies and services. In an effort to correct this, Contesting Illness engages critically with processes through which the meanings and effects of illness shape and are shaped by specific sets of practices. Featuring original contributions by researchers working in a number of disciplines, this collection examines intersections of power, contestation, and illness with the aid of various critical theoretical frameworks and methodological approaches. The contributors explore experiences of illness, diagnosis, and treatment, and analyse wider discursive and policy contexts within which people become ill and engage with health care systems. Though each essay is unique in its approach, they are linked together by a shared focus on contestation as a conceptual tool in considering the relationship between power and illness. Rather than focus on a single example, the contributors address different contested illnesses (chronic fatigue syndrome and environmental illness, for instance) as well as the contested dimensions of illnesses that are accepted as legitimate such as cancer and autism. Contesting Illness offers valuable insights into the assumptions, practices, and interactions that shape illness in the twenty-first century.